Implikasi Penerapan Perda Syariah terhadap Pluralisme di Indonesia - Suhli, Suhli; Wijaya, Septian Hendra; Muttaqin, Achmad Zahrul; Mujahadah , Arifatul (DIKTUM: Jurnal Syariah dan Hukum, 2022)
The application of sharia regulations in Indonesia causes disintegration of the unity and integrity of the Indonesian nation, this is because Sharia regulations are teachings of the Islamic religion. Even though Indonesia legally recognizes that Islam is not the only official religion in Indonesia. The heterogeneous and diverse composition of Indonesian society is a necessity and manifests itself as the identity of the Indonesian nation that must be preserved.The research method used in this study is a qualitative approach. The data collection technique used in this research is literature study. The data collected was collected through reading and studying the text (text reading), which was then compiled and then analyzed using descriptive analysis method with a deductive mindset. The results of this study are that the Sharia Regional Regulation as an instrument of regional law has major implications in people's lives, this is because it is binding on the local community. So it is important that the material contains the values ​​of Pancasila which have been the life philosophy of the Indonesian people. This is important to do to avoid disintegration between citizens which has been knitted by the founding fathers of the nation.